Ultra Wideband Radar for Respiratory Monitoring on Sleep Position - Mahardika T, Nurul Qashri; Ali, Erfansyah; Suratman, Fiky Yosef (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2021)
Sleep apnea is a sleep disorder that has a relation with respiratory system during sleep. One of the sleep apnea characteristic is suddenly stop breathing during sleep. People have the dierent of respiratory rate (RR) which is affected by sleep positions and body mass index (BMI).There are four sleep positions aecting the respiratory rate (RR). Polysomnography (PSG) is conventionally used to analysis the sleep apnea. This technique requires body contact that might be uncomfortable for the patient. In this study, the Xethru X4M200 radar sensor is proposed as non-contact tool to detect the RR by implementing the Doppler effect. Furthermore, the relation between RR with the sleep position and the BMI are discused. For that purpose, 20 participants (10 males and 10 females) with dierent BMIs and sleep positions are examined by monitoring their chest movement. This method is able to detect the indication of bradypnoea or tachypnoea. Futher systematic study and more participants are required to confirm our results and provide better non-contact technique for RR measurement.